Challenges of 10m air gun shooting among elite junior level athletes in Sri Lanka: current priorities and future interventions - Perera, K. K. S. T.; Madushani, A. A. L.; Perera, D. S. L. (Asian Exercise and Sport Science Journal, 2021)
The 10m Air Gun Shooting in Sri Lanka has produced a third highest number of Olympians in Sri Lanka. This research study has discovered the challenges of 10m Air Gun Shooting among elite junior level athletes in Sri Lanka respective to the current priorities and future intervention. Two specific objectives for instance to identify the physical, social, and economical challenges for developing 10-meter Air Gun shooting among elite junior level athletes in Sri Lanka and to identify current priorities then suggest future interventions. A Conceptual model of the study was accomplished by the comprehensive literature assessment.